The influence of sociodemographic factors and response style on caregiver report of infant developmental status - Connery, Amy K.; Raghunathan, Radhika S.; Colbert, Alison M.; Erdodi, Laszlo; Warschausky, Seth; Huth-Bocks, Alissa; Gerry Taylor, H.; Raghunathan, Trivellore; Berglund, Patricia; Staples, Angela D.; Lukomski, Angela; Kirkland, Jazmine; et al. (Frontiers in Pediatrics, 2023)
Caregiver report is the most feasible way to assess early childhood development but is susceptible to the influences of response style and sociodemographic factors. In a sample of 571 caregiver-infant dyads (47.8% female; 48% White), we compared caregiver reports on the Ages and Stages Questionnaire-Third Edition (ASQ-3) with reports on a novel, web-based assessment, PediaTrac™. Ratings on PediaTrac correlated with ratings on the ASQ-3 at all time points (2, 4, 6, and 9 months). Caregiver age, response style, and sociodemographic factors accounted for significant variance on both measures. Developmental reporting of early childhood skills is influenced by caregiver response style and sociodemographic factors. These influences must be considered in order to ensure the accurate identification of infant developmental status.